2013
DOI: 10.1590/s1676-06032013000200019
|View full text |Cite
|
Sign up to set email alerts
|

Histerídeos (Staphyliniformia: Coleoptera: Histeridae) dos Campos Gerais, Paraná, Brasil

Abstract: Histeridae is a group of beetles with diverse morphology known as generalist predators and which occurs in a wide variety of habitats. The objective of this paper was to present the first list of Histeridae from the Campos Gerais region (Parques Estaduais de Vila Velha, do Cerrado, e do Cânion Guartelá) and provide information about species from protected areas in the state of Paraná. Also were provided appropriate collecting methods for the group. The Histeridae from Campos Gerais are represented by 29 specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…It is intriguing that one of the major groups of Histeridae with a broad geographic distribution that is easily captured (e.g. pitfall trap and flight interception trap, Leivas et al (2013)) has only 15 species recorded from Brazil. Evidently the tribe has only reached the continent in recent times, with relatively little time to diversify.…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that one of the major groups of Histeridae with a broad geographic distribution that is easily captured (e.g. pitfall trap and flight interception trap, Leivas et al (2013)) has only 15 species recorded from Brazil. Evidently the tribe has only reached the continent in recent times, with relatively little time to diversify.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are important predators of eggs and larvae, particularly of Diptera (Cyclorrhapha). Some groups are related to other animals, particularly social insects such ants and termites (Leivas et al, 2013). Despite its ecological importance, few studies have been conducted in Brazil using this group, and the published ones focused on the systematics (Degallier et al, 2011;Corrêa et al, 2012;Leivas et al, 2012a, b;Leivas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Besides other bee killing beetles have been recorded in association with social bees (see Ellis et al 2003), melittophile clown beetles had never been reported either in single or in aggregations of natural beehives so far. This could occur due to Hololeptini having flattened body, which allows them to easily hide in small cavities and/or between the combs of beehives, as well as their negative phototropism and apparent low abundance in nature (see Leivas et al 2013). Although there is not enough information to determine both economic and ecological potential damages of clown beetles to natural and artificial beehives, their possible negative impact, especially H. reichii, cannot be discarded.…”
mentioning
confidence: 99%